Integrated metabolomic and gene expression analyses to study the effects of glycerol monolaurate on flesh quality in large yellow croaker (Larimichthys crocea). (15th January 2022) - Wang, Jing; Jiang, Huiqi; Alhamoud, Yasmin; Chen, Yong; Zhuang, Jiachen; Liu, Tao; Cai, Luyun; Shen, Weiliang; Wu, Xiongfei; Zheng, Weiqiang; Feng, Fengqin
Graphical abstract: Highlights: Glycerol monolaurate (GML) supplementation could significantly improve the flesh quality of Larimichthys crocea . A diet with 0.075% GML increased the non-essential amino acid and unsaturated fatty acid contents of Larimichthys crocea in muscle. The addition of GML dramatically augmented amino acid biosynthesis and metabolism. GML could activate the myogenic-related signaling pathway of Larimichthys crocea in muscle. Abstract: To improve the quality of cultured large yellow croaker ( Larimichthys crocea ), this study was performed to study the impacts of glycerol monolaurate (GML) on the nutritional value, growth performance, muscle texture, and taste intensity of L. crocea . The results showed that GML as a feed additive significantly increased the crude lipid content and reduced the diameters of muscle fibers, which in turn markedly altered the flesh texture in terms of cohesiveness. Moreover, the taste indicators (umami and richness) and flavor-related amino acid (glutamic acid, glycine, and proline) contents of L. crocea muscle were significantly higher in the GML group. Metabolomic and gene expression analyses showed that GML supplementation could significantly improve amino acid biosynthesis and metabolism, promote protein and lipid synthesis, and activate myogenic-related signaling pathways of L. crocea . Consequently, adding an appropriate amount of GML to fish feed would be conducive to providing healthy, nutrient-rich and acceptably flavored aquatic-products.